Pengaruh Insentif Kerja dan Motivasi Kerja terhadap Kinerja Karyawan Toko Yasfit - Ahmad Taufiqurrahman Asy'ari; Arief Noviarakhman Zagladi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This research aims to investigate the influence of work incentives and work motivation on employee performance at the Yasfit Store. The method used is a quantitative approach with a survey design, where data is collected through questionnaires distributed to 80 Yasfit Shop employees. Data analysis was carried out using multiple linear regression to test the proposed hypothesis. The research results show that work incentives have a positive and significant effect on employee performance with a significance value of 0.002, while work motivation also shows a significant positive effect with a significance value of 0.004. These findings indicate that increasing incentives and motivation can improve employee performance significantly. Therefore, Yasfit Store management is advised to design more attractive incentive programs and create a supportive work environment to increase employee motivation. It is hoped that this research can contribute to the development of human resource management strategies in the retail sector. Keywords : Incentives,Work Motivation, Employee Performance